EVALUATING CHEMISTRY TEXTBOOKS IN GHANAIAN SENIOR HIGH SCHOOLS: A FOCUS ON THE PRESENTATION OF QUALITATIVE ANALYSIS AND PERSPECTIVES OF TEACHERS AND LEARNERS - Nketsiah, John; Motlhabane, Abraham Tlhalefang (Universitas Negeri Surabaya, 2025)
This study investigated learner and teacher perspectives of chemistry textbooks, alongside a comparative analysis of textbook variations and the presentation of qualitative analysis concepts. A mixed-methods approach was employed, surveying 466 learners and 33 teachers, and evaluating three widely used chemistry textbooks in Ghana senior high schools. The findings revealed learners' positive perspectives of textbooks, but highlighted the need for enhanced visual and digital support. Teachers prioritized curriculum alignment and guidance, yet recognized gaps in concept representation. Textbook analysis exposed varying levels of comprehensiveness, presentation styles, and omissions. The study highlights the importance of considering learner and teacher perspectives, alongside textbook variations, to inform chemistry education. Recommendations include developing learner-centered textbooks, providing teacher professional development, and ensuring curriculum alignment and comprehensive concept representation. This research contributes to the ongoing effort to improve chemistry education, informing teachers, policymakers, and textbook developers. By addressing identified gaps, teachers can foster a deeper understanding of qualitative analysis concepts and promote effective learning outcomes.